Kekuatan Pembuktian Salinan Akta Auntentik Yang Dikeluarkan Oleh Notaris Pemegang Protokol - Safira, Azzah; Putra, Mohamad Fajri Mekka (Universitas Semarang, 2022)
This research aims to find out the strength of proofing authentic deed copies issued by Notary protocol holders. A copy can be trusted if in accordance with the original, the judge can order to show the original in advance of the trial with the approval of the Regional Supervisory Board. Notary protocol holders may issue copies. That a copy of the deed without minuta deed as a unit has no legal position especially as a means of evidence in civil cases. Minuta lost deed then the evidentiary force is submitted to the judge's consideration with a copy providing preliminary proof. The nature of prudence and transparency must be owned by notaries, should be in maintaining notary protocols, Notaries have tips so that protocols can be taken care of neatly and maintained This is because Notaries are officials who provide services to the community so that the community is calm and feel safe to have authentic evidence. The purpose of this study is to examine the strength of the proof of a copy of a deed made or issued by a non-Notary at the time the act was made, especially if the published copy does not have a deed minuta or the deed is lost. It vanishes where this is not the focus of the three previous studies above. Penelitian ini bertujuan untuk mengetahui kekuatan pembuktian Salinan akta autentik yang dikeluarkan oleh pemegang protokol Notaris. Salinan dapat dipercaya jika sesuai dengan yang aslinya, hakim dapat memerintahkan untuk menunjukan aslinya dimuka persidangan dengan persetujuan Majelis Pengawas Daerah. Pemegang protokol Notaris dapat mengeluarkan salinan akta. Bahwa Suatu salinan akta tanpa minuta akta sebagai satu kesatuan tidak memiliki kedudukan hukum terlebih sebagai alat bukti dalam perkara perdata. Minuta akta yang hilang maka kekuatan pembuktianya diserahkan kepada pertimbangan hakim dengan salinan memberikan pembuktian permulaan. Sifat kehati-hatian serta ketelitianya wajib dimiliki oleh Notaris, seharusnya dalam menjaga protokol Notaris, Notaris mempunyai kiat-kiat agar protokol dapat terurus dengan rapih dan terjaga Hal ini disebabkan Notaris merupakan pejabat yang memberikan pelayanan kepada masyarakat agar masyarakat tenang dan merasa aman untuk memiliki alat bukti yang autentik.